2020
DOI: 10.1093/humrep/deaa248
|View full text |Cite
|
Sign up to set email alerts
|

Fertility patients under COVID-19: attitudes, perceptions and psychological reactions

Abstract: Study question What are the perceptions of infertility patients and the factors correlating with their psychological distress, following suspension of fertility treatments during the COVID-19 pandemic? Summary answer Most patients preferred to resume treatment given the chance regardless of background characteristics; higher self-mastery and greater perceived social support were associated with lower distress, while feeling h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 48 publications
9
86
2
2
Order By: Relevance
“…In our study, more than two-thirds of women and men reported that they would be reassured if they knew when they could restart the IVF treatment. Similarly to our research, other authors demonstrated how a relevant proportion of patients would resume IVF treatment despite the COVID-19 pandemic [24,27].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, more than two-thirds of women and men reported that they would be reassured if they knew when they could restart the IVF treatment. Similarly to our research, other authors demonstrated how a relevant proportion of patients would resume IVF treatment despite the COVID-19 pandemic [24,27].…”
Section: Discussionsupporting
confidence: 87%
“…A cross-sectional questionnaire study included 168 patients whose fertility treatment was suspended following the COVID-19 pandemic in a tertiary hospital. Whereas demographic characteristics (such as age, marital status, parity, economic level, or duration of treatments) did not have a significant contribution, feeling helpless following the suspension of treatments was associated with higher distress; higher selfmastery and more significant perceived social support were associated with lower distress [27]. Clinic closure was appraised as stressful due to uncertainty and threat to the attainability of the parenthood goal.…”
Section: Discussionmentioning
confidence: 97%
“…The response rate of 29.2% was comparable to previous response rates reported on this topic ranging between 17 and 57% ( 22 – 24 ). Other studies utilizing social media recruiting strategies have reported higher response rates ( 5 , 25 ).…”
Section: Discussionsupporting
confidence: 84%
“…While quarantine (shelter in place) can be a necessary preventative measure during an infectious disease outbreak, it is often associated with a negative psychological impact ( 27 ). According to data published by Ben-Kimhy et al ( 24 ), Covid-19 has introduced new stressors and levels of anxiety for infertility patients. Closures of clinics, which resulted in deferred fertility treatments, led to a sharp increase in anxiety and depression among patients undergoing IVF ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, concern about delayed access to IVF treatments has become dramatically topical following the outbreak of the COVID-19 pandemic [17], which prompted the temporary suspension of treatments due to the limited knowledge on SARS-CoV-2 effects in pregnancy [18][19][20], generating higher distress in couples on the possible consequences that such "waiting period" could have on treatment outcomes [21,22].…”
Section: Introductionmentioning
confidence: 99%